e-TEP retroraumeninė pilvo sienos išvaržos plastika: chirurginė technika, artimiausia idealiajai - Mitevski, Aleksandar; Markov, Petar (Lietuvos chirurgija, 2020)
Introduction. Ventral hernia represents a problem for the surgeon and patients alike. eTEP repair is a technique that is minimally invasive, provides lower overall complication rates, decreased wound complications and the recurrence rates and shortens the length of stay in the hospital. Case. We present a case of a 48 year old patient who was admitted to our hospital for elective treatment of recurrent umbilical hernia. The patient had umbilical hernia repair 4 years ago, suture repair without mesh placement was performed according to the information given by the patient. On inspection there is visible supraumbillical scar, 12 cm in length with hernia bulging under the scar which is partially reducible on pressure. Discussion. The eTEP technique is closest to ideal because the abdominal cavity is not penetrated, is lessening the risk of visceral lesions and trocar site hernias, allows local or regional anesthesia, gives unsurpassed views of inguinal region and hernias and reproduces the technique of Rives-Stoppa. In favor to overcome the limitations deriving from the limited surgical field and restricted port set up, this technique has been modified based on the normal anatomy of the abdominal wall naming it dependently of the extension of the dissection and the location of the hernia. Conclusion. The extended-TEP (e-TEP) technique is based on the anatomical principle that the extraperitoneal space can be reached from almost anywhere in the anterior abdominal wall. It provides the most of the benefits for the patients but also requires great surgical skill and understanding of the anatomy of the anterior abdominal wall.